Digital Resistance to Social Media Taxation: A Semiotic Analysis of Protest Discourse on Platform X - Irwanto, Irwanto; Hariatiningsih, Laurensia Retno; Yunita, Ria; Irhamdhika, Gema; Bender, George Wilhelm (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2026)
This study examines netizen resistance to Indonesia's proposed 2026 social media tax policy. It employs a qualitative analysis of interactions on Platform X. This research employs van Leeuwen's (2015) social semiotics and W. Lance Bennett and Alexandra Segerberg's (2015) connective action theory, in analyzing how users construct collective resistance narratives. These narratives emerge through multimodal signs and personalized participation. Data from influential accounts, including @kompascom, @detikcom, and individual netizens, reveal three key resistance patterns. First, users construct injustice narratives using words like